2023
DOI: 10.1039/d3nj03280a
|View full text |Cite
|
Sign up to set email alerts
|

Arrays of graphene-quantum dots-supported DNA oligonucleotides as self-indicating porphyrin carriers

Abstract: The functionalization of deoxyribonucleic acid (DNA) with nanomaterials is a promising strategy to optimize the loading and efficiency of drugs in targeted clinical therapies. Herein we report a novel approach...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…Trindade and co-workers have combined carbon nanomaterials (e. g. GO sheets) with porphyrins and phthalocyanines to create nanosystems that detect DNA G-quadruplex. [27,129,130] The Raman imaging analysis on the GO/porphyrin nanosystem has shown that the porphyrin molecules are predominantly located at the edges of GO through electrostatic attractions and at the core through van der Waals and π-π stacking interactions. [27] The same analysis after the spectrofluorimetric titrations of the GO/porphyrin with DNA G-quadruplex led to fluorescence recovery because the porphyrin molecules linked through electrostatic interactions were detached from the surface of the nanosystem to interact with the G-quadruplex.…”
Section: Raman Imaging Of 2d Materials and Its Application In Sersmentioning
confidence: 99%
“…Trindade and co-workers have combined carbon nanomaterials (e. g. GO sheets) with porphyrins and phthalocyanines to create nanosystems that detect DNA G-quadruplex. [27,129,130] The Raman imaging analysis on the GO/porphyrin nanosystem has shown that the porphyrin molecules are predominantly located at the edges of GO through electrostatic attractions and at the core through van der Waals and π-π stacking interactions. [27] The same analysis after the spectrofluorimetric titrations of the GO/porphyrin with DNA G-quadruplex led to fluorescence recovery because the porphyrin molecules linked through electrostatic interactions were detached from the surface of the nanosystem to interact with the G-quadruplex.…”
Section: Raman Imaging Of 2d Materials and Its Application In Sersmentioning
confidence: 99%
“…Controlled reaction conditions prevent excessive grafting so that the biomolecules remain accessible for recognition. Amine-epoxides readily form under mild conditions to tether amino-modified oligonucleotides [ 55 ]. This provides an efficient approach to tethering amino-modified oligonucleotides or other amine-containing biomolecules.…”
Section: The Synthesis and Modification Of Graphene Materialsmentioning
confidence: 99%